UJI RESOLUSI SPASIAL PADA PERANGKAT LUNAK COMPUTED RADIOGRAPHY MENGGUNAKAN PENGOLAHAN CITRA DIGITAL - Hilmi Trian Setyawan; Suryono Suryono (Youngster Physics Journal, 2014)
This research conducted the spatial resolution of images in computed radiography using digital imagery. Spatial resolution testing aims to calculate the value of spatial resolution of computed radiography. The spatial resolution of images is useful to show the images of an object that is very useful for the smallest uphold the radiography diagnosis. The method used stars from doing expose on TOR CDR phantom with tube voltage variations, 70 kV, 72 kV, 74 kV, 76 kV, 78 kV, 80 kV, and 82 kV, read on computed radiography, the images is transferred to the computer software and then make a matlab program to calculate the spatial resolution of the image then performed to analysis. The results obtained images on the 70 kV has an average value of spatial resolution of 0,095 mm/pixel. This value is within the specified tolerance limit AAPM number 93 of 2006 which is less than 0,2 or 0,1 mm/pixel. Of spatial resolution values are not influence by tube voltage variation.Keywords: Spatial resolution, Phanthom TOR CDR, Matlab